Nursing appointment to the family of the child with autism spectrum disorder - Galvão, Dulce Maria Pereira Garcia (2018)
Galvão, D. Marques, C. Teixeira, D. & Cunha, M. Nursing appointment to the family of the child with autism spectrum disorder. 4th PNAE Congress on Paediatric Nursing, organizado pela PNAE, decorreria no dia 02 de Junho de 2018, em Atenas, Grécia.